Peningkatan Produktivitas dengan Relayout Area Produksi di UKM Keripik Tempe (Studi Kasus di UKM Suka Nicky, Banjarnegara) - Hidayat, Hety Handayani; Wijayanti, Nur; Prasetyo, Arif (Department of Agribusiness, Halu Oleo University, 2020)
SMEs are required to continue to make continuous improvements to increase productivity. One alternative that can be done is to re-layout the facilities and production areas. The main purpose of this research is to identify an increase in productivity with the proposed re-layout. Layout planning is carried out using the ARC (Activity Relations Chart) approach, the area requirements of each production facility, and the limitations of SMEs. From the results of the research conducted from January until March 2020, it is known that the proposed re-layout can improve material handling efficiency in Suka Nicky. Originally 219.75 meters which were taken in 148.5 minutes turned into 194.65 meters with a time of 117.5 minutes. With the decrease in distance and material handling time, the hope is that it can reduce the operational costs of SMEs.